PEMANFAATAN OPEN EDUCATIONAL RESOURCES (OER) DALAM TUTORIAL ONLINE - Afriani, Afriani (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
This article aims to present the results of analysis of the problems associated with the use of Open Educational Resources (OER) in the online tutorial at the Department of English Literature at Universitas Terbuka (UT). The method used is descriptive method to describe the actual situation in the presentation of the data and evaluate them to find answers to the research questions. The collected data have been described and studied in depth in order to obtain a greater understanding of research purposes. The research approach is a qualitative and quantitative approach. Merging the two approaches is the best way for each approach will be complementary. The data used is a questionnaire with closed questions and interviews. The findings indicate that OER contributes significantly in online tutorial and helps the participants to comprehend the material.